Minichromosome maintenance complex component 8 (MCM8) gene mutations result in primary gonadal failure. Issue 6 (14th April 2015) - Tenenbaum-Rakover, Yardena; Weinberg-Shukron, Ariella; Renbaum, Paul; Lobel, Orit; Eideh, Hasan; Gulsuner, Suleyman; Dahary, Dvir; Abu-Rayyan, Amal; Kanaan, Moien; Levy-Lahad, Ephrat; Bercovich, Dani; Zangen, David
Abstract : Background: Primary gonadal failure is characterised by primary amenorrhoea or early menopause in females, and oligospermia or azoospermia in males. Variants of the minichromosome maintenance complex component 8 gene ( MCM8 ) have recently been shown to be significantly associated with women's menopausal age in genome-wide association studies. Furthermore, MCM8 -knockout mice are sterile. The objective of this study was to elucidate the genetic aetiology of gonadal failure in two consanguineous families presenting as primary amenorrhoea in the females and as small testes and azoospermia in a male. Methods and results: Using whole exome sequencing, we identified two novel homozygous mutations in the MCM8 gene: a splice (c.1954-1G>A) and a frameshift (c.1469-1470insTA). In each consanguineous family the mutation segregated with the disease and both mutations were absent in 100 ethnically matched controls. The splice mutation led to lack of the wild-type transcript and three different aberrant transcripts predicted to result in either truncated or significantly shorter proteins. Quantitative analysis of the aberrantly spliced transcripts showed a significant decrease in total MCM8 message in affected homozygotes for the mutation, and an intermediate decrease in heterozygous family members. Chromosomal breakage following exposure to mitomcyin C was significantly increased in cells from homozygous individuals for c.1954-1G>A, as well as c.1469-1470insTA. Conclusions: MCM8, a component of the pre-replication complex, is crucial for gonadal development and maintenance in humans—both males and females. These findings provide new insights into the genetic disorders of infertility and premature menopause in women.